Le Pierres Taillees 1982. - Hastir, Arsene; Jullien, Jules (Les Avins-En-Condroz : [s.n.], 1982)
Ciglia, Cecco ; Jacques, Philippe ; Verstraete, Dees ; Palisot, Annie ; Croix, Roger La ; De Vestele, Marcus ; Marie, Baudoin Le ; Gilles, Jean-Marie ; Verhellen, Thierry ; Smolders, Michel ; Willequet, André ; Dessardo, Marco ; Rousseau, Etienne ; Jullien, Cécile ; Rousseau, Vincent ; Lallemand, Odon ; Rousseau, André ; de Caetera, Nicolas ; Verhellen, Thierry ; Perée, Michel ; Smolders, Quentin ; Maire, Baudoin Le ; Ciglia, Carmelina ; Dony, Victor ; Novis, Paul ; Claes, Frans ; Crombé, Patrick-Frederick ; Neimer, Serge ; Anciaux, Emmanuel ; Willequet, André
Frans
Pierres Taillees 1982, Les Avins-en-Condroz, du 29 mai au 20 septembre 1982
boek